Dry, wet depositions for ambient air nitrate, sulfate, and chloride ionic species at mixed (traffic, commercial, and residential) sampling sites in Central Taiwan. Issue 4 (2nd October 2019) - Fang, Guor-Cheng; Chen, Yu-Cheng; Kao, Chao-Lang; Zhuang, Yuan-Jie; Huang, Wen-Chuan; Lin, Wei-zuo
Abstract: This research was focused on the measurements of ambient air pollutants species (Cl −, NO3 −, and SO4 2− ) concentrations of wet and dry depositions by using PS-1 (TSP), dry depositions plate and wet depositions tub at mixed (traffic, commercial, and residential) sampling sites. Lu-Liao, characterized by traffic, commercial and residential sites, was selected as the dry deposition measurement site. Hungkuang University, characterized by a traffic site, was selected as the wet deposition collection site. At the Luliao site, the results indicated that the average ionic species (Cl −, NO3 −, and SO4 2− ) concentrations were 12.86, 25.58, and 18.37 μg/m 3, respectively, in winter and 2.94, 11.37, and 14.09 μg/m 3, respectively in spring. The average ionic species (Cl −, NO3 −, and SO4 2− ) dry depositions were 284.43, 1808.50, and 412.93 μg/m 2 min, respectively, in winter and 147.66, 109.59, and 415.44 μg/m 2 min, respectively, in spring. As for the monthly Cl −, NO3 −, and SO4 2− volume weighted mean (VWM) concentrations at the Hungkuang site, the results for January were 5.64, 4.41, and 10.13 mg/L, for May were 0.45, 1.98, and 2.09 mg/L, for June were 0.76, 1.39, and 2.46 mg/L, and for July were 1.83, 2.97, and 5.84 mg/L. The monthly Cl −, NO3 −, and SO4 2− Fw (Fluxwet deposition ) at the same site were 355.41, 277.63, and 638.15 mg/m 2 month, respectively, for January; 17.01, 99.03, and 362.05 mg/m 2 month, respectively, for May; 99.03, 181.18, and 319.45 mg/m 2 month, respectively, for June; and 362.05, 587.86, and 1156.49 mg/m 2 month, respectively, for July. SO4 2− had the highest VWM and Fw values when compared with the other ionic species, Cl − and NO3 − . The highest VWM values for all ionic species (Cl −, NO3 −, and SO4 2− ) all occurred in winter.